Evaluation of frailty in individuals aged 65 years and over, with and without diabetes: A cross-sectional study - Karsli , Zuhre; Pamuk, Gulseren; Ongel , Kurtulus (Annals of Medical Research, 2022)
Aim: This study aims to reveal the effect of frailty in patients aged 65 years and over with and without type 2 diabetes.Materials and Methods: A total of 298 elderly individuals aged 65 and over, 149 type 2 diabetic individuals and 149 non-diabetic individuals as the control group, were included in the descriptive cross-sectional study. Both groups were surveyed using Edmonton Frail Scale and socio-demographic data questionnaireResults: The mean age of the participants was 70.68±5.45 years, and 63.4% (n=189) of participants were female. Of the diabetic patients, 61 (40.9%) patients were found to be frail, 41 (27.5%) to be prone to frailty, and 47 (31.5%) to be non-frail. In individuals without diabetes, 33 (22.1%) individuals were found to be frail, 22 (14.8%) to be prone to frailty, and 94 (63.1%) to be non-frail. When both groups were analyzed statistically in terms of frailty, it was observed that frailty increased significantly in diabetic patients (p
Keywords: Diabetes; frailty; geriatrics